Gathering coconuts, Mayaro Beach, Trinidad, B.W.I. - Parker, J. (The Tourist and Exhibition Board of Trinidad and Tobago, 2010)
Laborers on Mayaro Beach, loading picked coconuts unto an ox cart.
Colour: Coloured (handpainted); Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Draft animals--Trinidad and Tobago; Carriages and carts--Trinidad and Tobago; Coconut industry--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Mayaro; Working class--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Oxen--Trinidad and Tobago; Painting--Trinidad and Tobago